Health Education terhadap Kemampuan Ibu Melakukan Toilet Training pada Anak Toddler di Posyandu Kemuning Desa Karangsono Kecamatan Loceret Kabupaten Nganjuk - Fitriasari, Betty (Journal of Global Research in Public Health, 2017)
The mother's ability to perform toilet training on toddlers is greatly influenced by her knowledge about toilet training. Improving the mother's knowledge about toilet training can be done through health education activities. The purpose of this study was to influence analysis health education on the ability of mothers to carry out toilet training on toddlers at the Kemuning Integrated Health Post, Karangsono Village, Loceret District, Nganjuk Regency. The design of this research is analytical observational with one group pre-post test approach. The population of this study was all mothers of toddlers at the Kemuning Integrated Health Post, Karangsono Village, Loceret District, Nganjuk Regency, totaling 40 mothers. The sample size obtained was 35 respondents. Sampling was carried out using purposive sampling technique.Data analysis using Wilcoxon test calculations at the α = 0.05 level. The results of the study showed that Most of the respondents at Posyandu Kemuning had the ability to do toilet training before health education at a low level, namely 25 mothers (71.4%). Most of the respondents at Posyandu Kemuning had the ability to do toilet training after health education at a moderate level, namely 23 mothers (65.7%). There is influence health education on the ability of mothers to toilet train toddlers at Posyandu Kemuning. This is proven by the p-value = 0.000 < α (0.05) so that the research hypothesis is accepted.